Photochemiresistor Sensor Development Based on a Bismuth Vanadate Type Semiconductor for Determination of Chemical Oxygen Demand - Alves, Nayara A. [UNESP]; Olean-Oliveira, André [UNESP]; Cardoso, Celso X. [UNESP]; Teixeira, Marcos F. S. [UNESP] (American Chemical Society (ACS), 2020)
The present paper describes the development of a novel photochemiresistor sensor for the determination of chemical oxygen demand (COD). A chemiresistive device was produced by a thin film of the monoclinic phase of bismuth vanadate deposited on an FTO glass surface. The resistive properties of the photosensor were carried out by electrochemical impedance spectroscopy (EIS). The electrical resistance of the platform was dependent on the presence of organic material in aqueous solution and the incidence of light. The decrease in resistance can be explained by considering that by increasing the amount of organic material, the amount of charge transferred to BiVO4 increases, as does the amount of the photogenerated conduction band on the film. This behavior is not observed when carrying out the same measurements in the absence of light. Under the optimal experimental conditions, the linear response of the chemiresistor sensor is between 0.20 and 19.9 mg L-1 COD at a fixed AC frequency of 0.1 Hz. There is a good correlation between the charge transfer resistance and COD concentration in the electrolyte solution. Quantification of COD in waste and lake waters was successfully performed using the novel photochemiresistor sensor. The results achieved in the analysis with the sensor are in accordance with the conventional method.
Keywords: environmental sensor; impedance; photoelectrochemical; semiconductor resistor; sensor technology